An fMRI study of perception and action in deaf signers. (February 2016) - Okada, Kayoko; Rogalsky, Corianne; O'Grady, Lucinda; Hanaumi, Leila; Bellugi, Ursula; Corina, David; Hickok, Gregory
Abstract: Since the discovery of mirror neurons, there has been a great deal of interest in understanding the relationship between perception and action, and the role of the human mirror system in language comprehension and production. Two questions have dominated research. One concerns the role of Broca's area in speech perception. The other concerns the role of the motor system more broadly in understanding action-related language. The current study investigates both of these questions in a way that bridges research on language with research on manual actions. We studied the neural basis of observing and executing American Sign Language (ASL) object and action signs. In an fMRI experiment, deaf signers produced signs depicting actions and objects as well as observed/comprehended signs of actions and objects. Different patterns of activation were found for observation and execution although with overlap in Broca's area, providing prima facie support for the claim that the motor system participates in language perception. In contrast, we found no evidence that action related signs differentially involved the motor system compared to object related signs. These findings are discussed in the context of lesion studies of sign language execution and observation. In this broader context, we conclude that the activation in Broca's area during ASL observation is not causally related to sign language understanding. Highlights: Perception and production of American Sign Language (ASL) was examined in native deaf signers using fMRI. Deaf signers activated a network of language areas during perception and production of ASL. Overlap was found in Broca's area, middle temporal and inferior parietal regions.